2014
DOI: 10.1186/1129-2377-15-63
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 5-HT3 receptors and TTX resistant sodium channels (NaV1.8) on muscle nerve fibers in pain-free humans and patients with chronic myofascial temporomandibular disorders

Abstract: BackgroundPrevious studies have shown that 5-HT3-antagonists reduce muscle pain, but there are no studies that have investigated the expression of 5-HT3-receptors in human muscles. Also, tetrodotoxin resistant voltage gated sodium-channels (NaV) are involved in peripheral sensitization and found in trigeminal ganglion neurons innervating the rat masseter muscle. This study aimed to investigate the frequency of nerve fibers that express 5-HT3A-receptors alone and in combination with NaV1.8 sodium-channels in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 51 publications
0
34
0
1
Order By: Relevance
“…Several studies have been conducted to determine the principle and mechanism through which TMD physically and psychologically affects patients. Christidis et al discovered that 5-HT3A(serotonin)-receptor, an important pain transmitter, exists in high levels in the masseter and tibialis muscles, and women with TMD possess more nerve fibers releasing 5-HT3A-receptors [ 58 ]. Also, Ojima et al revealed that genetic factors involved in serotonin transport modulate serotonin secretion, with consequent potential to act as a catalyst in pathological expression of TMD [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to determine the principle and mechanism through which TMD physically and psychologically affects patients. Christidis et al discovered that 5-HT3A(serotonin)-receptor, an important pain transmitter, exists in high levels in the masseter and tibialis muscles, and women with TMD possess more nerve fibers releasing 5-HT3A-receptors [ 58 ]. Also, Ojima et al revealed that genetic factors involved in serotonin transport modulate serotonin secretion, with consequent potential to act as a catalyst in pathological expression of TMD [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that 5-HT activates the 5-HT 3 -receptor to mediate muscle pain and mechanical sensitivity [ 13 15 ]. In a recent study it was shown that the 5-HT 3A -receptor is highly expressed in human masseter muscles and that more nerve fibers express 5-HT 3A -receptors in women with M-TMD compared to healthy women [ 16 ]. Therefore, targeting peripheral 5-HT 3 -receptors with drugs that block these receptors could be an interesting therapeutic approach for chronic muscle pain.…”
Section: Introductionmentioning
confidence: 99%
“…5-HT exerts its effect by activating different receptors, grouped into 5-HT 1 -to 5-HT 7 -receptors (1). The 5-HT 3 -receptor is widely distributed on neurons both in the brain and peripherally and participates in nociception supraspinally, spinally, and in the periphery (2)(3)(4). 5-HT 3 -antagonists, such as granisetron, ondansetron, and tropisetron, are commonly used treat radiotherapy-and chemotherapy-induced vomiting and nausea (5).…”
Section: Discussionmentioning
confidence: 99%